Peningkatan Hasil Belajar dalam Pembelajaran IPS Menggunakan Model Make A Match Di Kelas V - Putri, Tria Yowanda; Reinita, Reinita; Arwin, Arwin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2016)
The purpose of this study was to describe and increase in student learning outcomes in social studies learning by using the Make a Match model in the fifth grade of elementary school. Types of this research was classroom action research with qualitative and quantitative approach. The research subject was 24 grade V students. The research procedure consistend of planning, implementing, observing, and reflecting. The result of the study showed and increase in aspects: a) RPP cycle I with an average of 76,78% and cycle II 92,85%, b) implementation on the aspect of the teacher cycle I with an average of 79,62% and the second cycle 84,37%, the aspect of the students of the first cycle with an average 76,56% and cycle II 87,5%, c) learning outcomes in the first cycle with an average of 73,31% and cycle II 83,71%. The conclusions from the result of the research conducted are using the Make a Match model can improve student learning outcomes in social stundent learning in class V SD Negeri 21 PPA Solok.Keywords : Make a Match, learning outcomes, elementary school.